SIFAT MEKANIK PADA SAMBUNGAN KAYU NYATOH (Palaquium xanthochymum Pierre) BERDASARKAN BENTUK SAMBUNGAN DAN MACAM ALAT SAMBUNG - to, Yan; Usman, Fadillah. H.; Yani, Ahmad (JURNAL HUTAN LESTARI, 2014)
The wood with a long stretch increasingly scarce, so their use limited variety. Therefore it is necessary for splicing. Jointed wood has lower strength than wood intact, because of shift caused among other selection shape and the lack of proper connecting equipment in a construction. Two factors of treatment in this research are shape the connection (connection angled lip hooked and lip straight connection) and type of connecting tools (pegs, nails and bolts) with three replications. Measured parameters in this study are the mechanical properties of wood connections on the static bending persistence and determination of bending fracture. The sample size is (W) 5 cm x (H) 5 cm x (L) 76 cm. Then testing the Modulus of Elasticity (MOE) and the Modulus of Rupture (MOR). The results showed that the value of the MOE decreased 81.31% - 90.45% and MOR 81.71%- 91.55% Â value also decreased when compared with the control and the value entered in the category of strong wood class V. The low value of the MOE and MOR is found in the connecting tool like pegs and bolts. Thus resulting in the dissolution of the wood fibers and consequently the strength of the connections is low. Then the tool also decreases the strength of nails connecting wood used due to the small diameter of nail (2.8 mm) and use only two sticks nails in one connection. Results of this research on the wood connection with the treatment Nyatoh wood (Palaquium xanthochymum Pierre) used for construction purposes only under the roof only, for example gording, murplat, and plafond which is supported by the use of pillar. Â  Keyword: Mechanical properties, connection, connection forms, kinds of tools connecting